Transgenic approaches to control self-incompatibility in Petunia hybrida - Sharef, Ashtekhwaz Ahmad (2017)
Petunia hybrida belongs to the family Solanaceae and is an important horticultural crop grown worldwide. Petunia hybrida and one of its parental species, Petunia inflata, are also established model organisms for the study of gametophytic self-incompatibility (SI). All members of the Solanaceae, including Petunia, share the S ribonuclease mechanism of self-incompatibility. The pistil phenotype is determined by an extracellular stylar ribonuclease or “S-RNase”. The pollen phenotype is determined by several S-linked F-box genes (SLFs). All these genes are tightly linked at the S-locus to form an “S-haplotype”. Most cultivated Solanaceae exhibit self-compatibility (SC) as this greatly facilitates the production of seed for annual crops. SC can arise from the breakdown of a functional SI system during domestication and breeding. In this PhD project, we have attempted to develop approaches to control SI in Petunia. Several stocks of Petunia that exhibit SI are available at the University of Nottingham. These carry five distinct S-haplotypes with corresponding S-RNase sequence data, three in P. inflata (PiS3, PiSk1, PiSd) and two in P. hybrida (PhS3L, PhSv). Our approach to engineer SC into lines with SI involved the introduction of a heterologous SLF gene from Antirrhinum hispanicum. It has previously been shown that transformation of P. hybrida with the AhSLF-S2 gene under the control of a pollen-specific promoter (LAT52) causes SI to breakdown (Qiao et al, 2004b). This is explained as a “competitive interaction”. We have obtained the LAT52: AhSLF S2 construct used by the group of Prof. Yongbiao Xue (Chinese Academy of Sciences, Beijing). In addition, we have obtained three constructs containing other SLF family members (AhSLF-S2C, AhSLF-S4D and AhSLF-S1E) all expressed specifically in pollen (Zhou et al, 2003). The aim of this project is to extend the analysis of these heterologous SLF genes to test whether they offer a general approach to overcome SI in P. hybrida. This involved using the wider range of S haplotype stocks available (5) and the full range of constructs available (4). Initial experiments confirmed the genotype and phenotype of the P. inflata stocks. Crosses were made between P.hybrida and P.inflata and the resulting F1 progeny were tested for SI. It was noticed that some progeny inheriting the PiSd allele of P. inflata have a tendency towards SC, but others have a stable SI phenotype. This observation was further analysed in the F2 generation and based on reciprocal crosses it was determined that the pollen part of the PiSd allele had lost its function resulting in compatibility. Prior to transformation the constructs were checked by sequencing plasmid DNA and colony PCR products using specific primers. The expected fusions of SLF gene and LAT52 promoter were confirmed. An established protocol was used to transform the S3/Sv genotype of P. hybrida. Different numbers of transgenic plants have been identified for each construct (6, 17, 3 and 11 for AhSLF-S2, AhSLF-S2C, AhSLF-S1E and AhSLF-S4D respectively). However, in the T0 generation competitive interaction was not observed. Transgenic plants were crossed with Petunia inflata but F1 hybrid plants remained SI. Transgenic plants obtained for AhSLF-S2 and AhSLF-S1E were analysed in the T1 generation. In spite of the fact that all plants derived from PhSLF-S2 remained SI, one plant derived from AhSLF-S1E became SC. It was predicted that the compatibilty in this particular plant arises as a result of homozygosity. Based on this observation a hypothesis was proposed for a relationship between compatibility and homozygosity and several techniques were used to test this hypothesis. It has been concluded that there is a relationship between homozygosity and transgene behaviour in specific epigenetic situations.